PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS DO IT YOURSELF HOME PROJECT BAGI GURU TK ISLAMIC KIDS CORNER BOGOR - Fauzy Kosasih; Juhana Juhana; Lidwina Sri Ardiasih; Rahayu Dwi Riyanti; Suratinah Suratinah (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service program aims to train Bogor Islamic Kids Corner (IKC) Kindergarten teachers to develop DIY home project-based learning media for students. This activity involves partners consisting of teachers and students in partner schools. This activity begins with an initial visit to analyze the situation and needs of the local community. From the results of the visit, it was identified and agreed that community service activities (Abdimas) were focused on developing learning media based on the DIY home project considering that teaching and learning activities were still carried out from home (emergency learning). From the results of the implementation of Abdimas activities, it can be reported that from four training sessions with IKC Kindergarten teachers, the teachers have been able to develop and utilize DIY home project-based learning media with students. Both teachers and students were enthusiastic and active in participating in every series of community service activities while still adhering to health protocols.   Program pengabdian kepada masyarakat dengan judul IbM Pengembangan Media Pembelajaran Berbasis DIY Home Project bagi Guru TK IKC Bogor ini bertujuan melatih guru TK Islamic Kids Corner (IKC) Bogor untuk mengembangkan media pembelajaran berbasis DIY home project bagi siswa. Kegiatan ini melibatkan mitra yang terdiri dari para guru dan siswa di sekolah mitra. Kegiatan ini dimulai dengan kunjungan awal untuk menganalisis situasi dan kebutuhan masyarakat di lokasi. Dari hasil kunjungan berhasil diidentifikasi dan disepakati bahwa kegiatan pengabdian kepada masyarakat (PkM) difokuskan pada pengembangan media belajar berbasis DIY home project mengingat kegiatan belajar mengajar masih dilakukan dari rumah (pembelajaran jarak jauh). Dari hasil pelaksanaan kegiatan PkM, dapat dilaporkan bahwa dari empat kali pelatihan dengan para guru TK IKC maka para guru telah mampu mengembangkan dan memanfaatkan media pembelajaran berbasis DIY home project bersama para siswa. Baik para guru maupun para siswa antusias dan aktif dalam mengikuti setiap rangkaian kegiatan PkM dengan tetap menaati protokol kesehatan.